Beaumaris Castle - Master James of St. George
At the rear of the gatehouse, and within the inner wall which was similarly protected with towers, stood the hall keep. It had a great hall on its first floor and service rooms beneath. The garrison of such a castle included then men at arms- the equivalent in rank of Norman Knight- twenty archers, and a hundred foot soldiers, but this number could be increased in an emergency.